1997
DOI: 10.1017/s0889189300007165
|View full text |Cite
|
Sign up to set email alerts
|

Local food systems and sustainable communities

Abstract: The long-term health of a community's food system is an important indicator of its vitality and sustainability. A logical and appropriate way to revitalize a community is by the development of a local food economy. People throughout the United States are designing and implementing sustainable, local food systems that are rooted in particular places, aim to be economically viable for farmers and consumers, use ecologically sound production and distribution practices, and enhance social equity and democracy for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
292
0
14

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 469 publications
(310 citation statements)
references
References 8 publications
4
292
0
14
Order By: Relevance
“…CSA is considered a 'win-win' for farmers and consumers. Farmers gain a direct market while members have greater access to seasonal and diverse local foods, and opportunities to know and trust the source of their foods (15)(16)(17) .…”
mentioning
confidence: 99%
“…CSA is considered a 'win-win' for farmers and consumers. Farmers gain a direct market while members have greater access to seasonal and diverse local foods, and opportunities to know and trust the source of their foods (15)(16)(17) .…”
mentioning
confidence: 99%
“…The benefits and potential of urban farming towards the community can be categorised into four, which are environmental stewardship (Lydecker & Drechsel, 2010;HB Lanarc-Golder, 2013), economic reliance (Giedych, 2015;Lyson, Gillespie & Hilchey, 1995), social improvement (Scott, 2015;Sharp, Imerman & Peters, 2002;Feenstra, 1997) as well as health and nutrition (Kumar, 2015). Cabannes (2006) reported that urban farming is also an investment strategy in developed countries to bring urban people back to nature, opening eyes and minds to the global issues, and to educate children from the natural cycle of life through landscape environment.…”
Section: Benefits and Potential Of Urban Farmingmentioning
confidence: 99%
“…For example Marsden et al, (1999), Ross et al (1999), Marsden et al (2000), Hinrichs (2003), Winter (2003), and Ikerd (2005) have all suggested that expansion of local foods may be a development strategy for rural areas, particularly those areas that have experienced negative effects of globalization. And while many scholars have highlighted the importance of local food systems to regional economies (Feenstra 1997;Trobe 2001;Renting et al 2003;Star et al 2003;Bhatia and Jones 2011), few have sought to exploit recent theoretical frames advanced by researchers from the fields of economic geography and regional science; the fields most concerned with regional economic development. The concept of local and regional foods as a regional development strategy and, by extension, the analysis of regional food systems in the context of the city-region, present a unique theoretical lens of which new insights into the factors that influence the emergence of such systems can be examined.…”
Section: 1: Overviewmentioning
confidence: 99%